Pengaruh Harga dan Kulitas Pelayanan terhadap Kepuasan Pelanggan : Studi Kasus pada Mixue cabang Pasar Bersih, Jababeka - Rafi’ah Kumalasari; Anang Lukmana; Jamaludin Jamaludin; Pupung Purnamasari (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
The aim of this research is to determine the impact of the influence of price and quality of service on customer satisfaction (case study at Mixue Pasar Bersih branch, Jababeka). The research method used is quantitative using hypothesis testing to analyze the relationship between the variables studied. The population used as research objects are consumers who buy Mixue products at the Jababeka Clean Market. Data analysis was implemented in the form of a questionnaire using the SPSS application with the tests used being the Validity Test and Reliability Test. Total respondents were 113 people from 15 questions, considering the questionnaire answers which stated Strongly Agree 23%, Agree 46%, Normal 24%, Disagree 5%, Strongly Disagree 1%. The results of the research state that X1 has an effect on Y and is supported by variable X2 which also has an effect on Y.